In vitro AMPK activating effect and in vivo pharmacokinetics of mogroside V, a cucurbitane-type triterpenoid from Siraitia grosvenorii fruits. Issue 9 (18th January 2016) - Luo, Zuliang; Qiu, Feng; Zhang, Kailun; Qin, Xijun; Guo, Yuhua; Shi, Hongwu; Zhang, Lixia; Zhang, Zhonglian; Ma, Xiaojun
Abstract : The aim of this study was to explore the anti-diabetic effects of mogroside V (MV) and its aglycone mogrol (MO), both isolated from the fruits of Siraitia grosvenorii Swingle, and to investigate the pharmacokinetic behaviors of MV and its metabolite MO in rats. Abstract : The aim of this study was to explore the anti-diabetic effects of cucurbitane-type triterpenoids, mogroside V (MV) and its aglycone mogrol (MO), both isolated from the fruits of Siraitia grosvenorii Swingle, and to investigate the pharmacokinetic behaviors of MV and its metabolite MO in rats. The anti-diabetic effects by activating AMPK of MV and MO were evaluated in this study. Furthermore, a sensitive and specific liquid chromatography electrospray ionization-tandem mass spectrometry method for the simultaneous quantification of MV and its metabolite MO in rat plasma has been developed and validated. The assay has been successfully used for pharmacokinetic evaluation of MV and its metabolite MO after intravenous and oral administration of a single dose of MV in rats at 2.0 mg kg −1 and 5.0 mg kg −1, respectively. In vitro activities indicated that MV and its aglycone MO were both potent AMPK activators. MV and MO could activate the AMPK heterotrimer α2β1γ1 by 2.4 and 2.3 fold with an EC50 of 20.4 and 4.2 μM, respectively. This result suggested AMPK activation by MV and MO was proved to contribute at least partially to the anti-diabetic properties of S. grosvenorii . The pharmacokinetic results showed that MV was rapidly deglycosylated and metabolized into MO, and both of these were determined after intravenous administration of 2.0 mg kg −1 of MV in rats. MV was not detected in rat plasma after oral administration, whereas a trace amount of MO was found. The oral absolute bioavailability ( F ) of MV was estimated to be 8.73 ± 1.46% and the elimination half-life ( t 1/2 ) of metabolite MO in rats was 2.46 ± 0.19 h. It was indicated that MV showed poor absorption and/or strong metabolism in vivo . Its metabolite MO may be the main pharmacological activity form after oral administration of MV in rats.